2016
DOI: 10.1038/srep28210
|View full text |Cite
|
Sign up to set email alerts
|

Negative autoregulation of BMP dependent transcription by SIN3B splicing reveals a role for RBM39

Abstract: BMP signalling is negatively autoregulated by several genes including SMAD6, Noggin and Gremlin, and autoregulators are possible targets for enhancing BMP signalling in disorders such as fibrosis and pulmonary hypertension. To identify novel negative regulators of BMP signalling, we used siRNA screening in mouse C2C12 cells with a BMP-responsive luciferase reporter. Knockdown of several splicing factors increased BMP4-dependent transcription and target gene expression. Knockdown of RBM39 produced the greatest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…This gene functions in the negative autoregulation of BMP4 (Faherty et al. ); in birds, the expression and regulation of BMP is important in the diversification of bill shapes (Abzhanov et al. ; Wu et al.…”
Section: Discussionmentioning
confidence: 99%
“…This gene functions in the negative autoregulation of BMP4 (Faherty et al. ); in birds, the expression and regulation of BMP is important in the diversification of bill shapes (Abzhanov et al. ; Wu et al.…”
Section: Discussionmentioning
confidence: 99%
“…We analysed GATAD2A–FLAG protein immunoprecipitation by mass spectrometry and found that multiple components of the NuRD complex also co-immunoprecipitated with GATAD2A (Supplementary Table 5 ). Of the GATAD2A-associated CAPs, ZNF219 38 , SMAD4 39 , and RARA 40 have previously been associated with the NuRD complex (Fig. 5c ).…”
Section: Known and Novel Cap Associationsmentioning
confidence: 96%
“…While isoform 2 (NP_001284524) likely represents the principal SIN3B isoform in humans, alternative splicing produces multiple SIN3B isoforms in mouse (38,39) and it was reported that ratios of human SIN3B gene products are responsive to cellular queues (38).…”
Section: Protein Domain Organization Is Partially Conserved Between Smentioning
confidence: 99%